SHEAR WAVE 〓 STRUCTURE FOR THE LITHOSPHERE IN THE LUTZOW-HOLM BAY REGION, EAST ANTARCTICA - カナオ, マサキ; アカマツ, ジュンペイ; KANAO, Masaki; AKAMATSU, Junpei (National Institute of Polar Research, 1995)
P(論文) Seismic wave attenuation in the lithosphere has been studied in various regions by the analysis of coda amplitudes of S-waves for local earth-quakes. On the basis of the observed facts, the attenuation factor of coda waves (〓_c) is assumed to reflect the averaged 〓 for S-waves (〓_s) in an area within the ellipsoid of the scattering medium in the lithosphere. In this study, layered models of 〓_s for the lithosphere in two tectonically different regions of shield and island arc were estimated from the observed 〓_c at the various lapse times defined as 'time from origin of earthquake'. As for the representative of stable shield regions, five shallow earthquakes observed with a local telemetry seismic network around the Lutzow-Holm Bay region, East Antarctica, were re-analyzed to calculate 〓_c for the lapse time ranging from 20s to 70s in the 4,8 and 16Hz frequency bands. As for the tectonic active island arc region, 〓_c for intra-plate earthquakes observed by the telemetered network in the middle and northern Kinki district, Japan was found in eight lapse time ranges from 20s to 85s at the same three frequency bands. From the resultant 〓_s structure in both regions, it is remarkable that (1) 〓_s for each layer of the same depth in the Lutzow-Holm Bay region takes larger values than those of the Kinki district, particularly in high frequency range; (2) 〓_s for the Lutzow-Holm Bay region has a stronger frequency dependency than in the Kinki district. Another noticeable point is that 〓_s for both regions has a rapid increase near the surface layer, which is attributed to the dependence of 〓_c on lapse time in the short lapse time range. This is predominant in the Kinki district where 〓_s is characterized by low values in the surface layer and a noticeable increase with depth in the upper 5km of the crust. departmental bulletin paper